2020
DOI: 10.1101/2020.11.25.396069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environment-driven reprogramming of gamete DNA methylation occurs during maturation and is transmitted intergenerationally in salmon

Abstract: An epigenetic basis for transgenerational plasticity is widely theorized but convincing empirical support is limited by taxa-specific differences in the presence and role of epigenetic mechanisms. In teleost fishes, DNA methylation does not undergo extensive reprogramming and has been linked with environmentally-induced intergenerational effects, but solely in the context of early life environmental differences. Using whole genome bisulfite sequencing, we demonstrate that differential methylation of sperm occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Among the most important applications of RNA-Seq currently used is testing for rapid adaptation to environmental change (e.g., to captivity or climate warming), and to determine if environmentally-induced gene expression shifts are transgenerationally transmitted (e.g., Christie et al 2016, Charlesworth et al 2017, Skvortsova et al 2018, Navarro-Martin et al 2020, Savilammi et al 2020. Our results will facilitate future research testing for transgenerational transmission of potentially epigenetic hatchery-adaptive traits in wild fish populations (e.g., Christie et al 2016, Le Luyer et al 2017, Wellband et al 2020.…”
Section: Discussionmentioning
confidence: 85%
“…Among the most important applications of RNA-Seq currently used is testing for rapid adaptation to environmental change (e.g., to captivity or climate warming), and to determine if environmentally-induced gene expression shifts are transgenerationally transmitted (e.g., Christie et al 2016, Charlesworth et al 2017, Skvortsova et al 2018, Navarro-Martin et al 2020, Savilammi et al 2020. Our results will facilitate future research testing for transgenerational transmission of potentially epigenetic hatchery-adaptive traits in wild fish populations (e.g., Christie et al 2016, Le Luyer et al 2017, Wellband et al 2020.…”
Section: Discussionmentioning
confidence: 85%
“…Early environment is a deterministic factor that acts on later performance in fish (Jonsson, & Jonsson, 2009). Accordingly, mounting evidence points toward an epigenetic basis associated with the effect of hatchery environment on epigenetic reprogramming of the progeny produced in captivity (Christie et al, 2016; Gavery et al, 2018; Le Luyer et al, 2017; Leitwein et al, 2021; Wellband et al, 2021). Of particular interest is the study of Rodriguez‐Barreto et al (2019), which showed that early‐life hatchery exposure changed the pattern of methylation of Atlantic salmon males and that corticotropin‐releasing factor receptor 1‐like was one of the differentially methylated regions in hatchery fish.…”
Section: Discussionmentioning
confidence: 99%
“…Early environment is a deterministic factor that acts on later performance in fish (Jonsson, & Jonsson, 2009). Accordingly, mounting evidence points toward an epigenetic basis associated with the effect of hatchery environment on epigenetic reprogramming of the progeny produced in captivity (Christie et al, 2016;Gavery et al, 2018;Le Luyer et al, 2017;Leitwein et al, 2021;Wellband et al, 2021). Of particular interest is the study of Rodriguez-Barreto et al…”
Section: Reduced Fitness Of Captive-bred Atlantic Salmon Stocked At T...mentioning
confidence: 99%
“…Early environment is a deterministic factor that acts on later performance in fish (Jonsson & Jonsson, 2014). Although differences in fitness between hatchery-reared and wild salmon were previously thought to be genetically based only, mounting evidence also points toward an epigenetic basis associated with the effect of hatchery environment on epigenetic reprogramming of the progeny produced in captivity (Christie et al 2016; Le Luyer et al 2017; Gavery et al 2018; Wellband et al 2021; Leitwein et al 2021). Of particular interest is the study of Rodriguez Barreto et al (2019) which showed that early-life hatchery exposure changed the pattern of methylation of Atlantic salmon males and that corticotropin-releasing factor receptor 1-like was one of the differentially methylated regions in hatchery fish.…”
Section: Discussionmentioning
confidence: 99%